2021
DOI: 10.1016/j.cpr.2020.101938
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of PTSS under the influence of public health emergencies in last two decades: A systematic review and meta-analysis

Abstract: Background Since the beginning of 21st century, several major public health emergencies (PHEs) have threatened the health of people globally. Posttraumatic stress symptoms (PTSS) was one of the most concerned mental health problems. The objective of this study is to systematically estimate the prevalence of PTSS under the influence of PHEs. Method We searched both English and Chinese databases. This meta-analysis used a random-effects model to estimate the prevalence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 63 publications
(50 reference statements)
0
13
1
1
Order By: Relevance
“…The presence of mental problems could be delayed relative to the occurrence of a traumatic event [28]. Meanwhile, mental problems could exist for a long time after the trauma [29,30]. To more precisely determine the longitudinal trajectory of psychological problems related to the COVID-19 epidemic, future studies should conduct follow-up studies and also examine the protective and risk factors towards the psychological problems.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of mental problems could be delayed relative to the occurrence of a traumatic event [28]. Meanwhile, mental problems could exist for a long time after the trauma [29,30]. To more precisely determine the longitudinal trajectory of psychological problems related to the COVID-19 epidemic, future studies should conduct follow-up studies and also examine the protective and risk factors towards the psychological problems.…”
Section: Discussionmentioning
confidence: 99%
“…The repeated outbreaks of COVID-19 and its rapid transmission worldwide placed enormous pressure on the health care system and its professionals [ 2 6 ]. Health care workers in China faced great challenges during the severe pandemic, such as a wide knowledge gap of viral pathophysiology and the unprecedented local breakdown of protective equipment supplies [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the control of epidemic and care of patients are the most crucial tasks, new research is now suggesting that there may be long-term consequences, such as fatigue or muscle weakness, sleep difficulties, anxiety or depression, in those 60 million people who recovered from COVID-19 infections [ 7 ]. Crucially, COVID-19 survivors who experienced fear for survival, are vulnerable to develop post-traumatic stress symptoms (PTSS) [ 8 10 ]. A recent study found that COVID-19 survivors in Italy suffered severe PTSS shortly after they were discharged (e.g., within 1 month) from the hospital [ 9 ].…”
Section: Introductionmentioning
confidence: 99%